2022
DOI: 10.3390/bios12040198
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal Polymeric Microneedle Sensing Platform for Fentanyl Detection in Biofluid

Abstract: Opioid drugs are extremely potent synthetic analytes, and their abuse is common around the world. Hence, a rapid and point-of-need device is necessary to assess the presence of this compound in body fluid so that a timely countermeasure can be provided to the exposed individuals. Herein, we present an attractive microneedle sensing platform for the detection of the opioid drug fentanyl in real serum samples using an electrochemical detection method. The device contained an array of pyramidal microneedle struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…11 Moreover, Joshi et al proposed an interference-free fentanyl detecting assay using microneedles, the sensing performance of which was verified in diluted serum. 89 Similarly, in situ monitoring of apomorphine 90 and levodopa 91 has also been validated in microneedles, providing attractive tools for drug abuse control.…”
Section: Equipment-assisted Microneedle Sensorsmentioning
confidence: 99%
“…11 Moreover, Joshi et al proposed an interference-free fentanyl detecting assay using microneedles, the sensing performance of which was verified in diluted serum. 89 Similarly, in situ monitoring of apomorphine 90 and levodopa 91 has also been validated in microneedles, providing attractive tools for drug abuse control.…”
Section: Equipment-assisted Microneedle Sensorsmentioning
confidence: 99%
“…These devices can generate micrometer-scale pathways in the stratum corneum, the topmost layer of the epidermis, for body fluid extraction. [1,[3][4][5] Numerous studies reported on the design of MN patches for transdermal drug delivery and biosensing. For example, Chua et al described the skin penetration and ISF collection parameters that were associated with various shapes of MN arrays.…”
Section: Introductionmentioning
confidence: 99%
“…These devices can generate micrometer‐scale pathways in the stratum corneum, the topmost layer of the epidermis, for body fluid extraction. [ 1,3–5 ]…”
Section: Introductionmentioning
confidence: 99%
“…Compared to other approaches, voltammetric studies are observed to be more precise, explanatory, and cost-effective. 17 A few previous studies report a <1 nM detection limit (LOD) for H 2 O 2 sensing; nonenzymatic H 2 O 2 sensing has demonstrated sensitivity in the micro−millimolar range. 18−22 Previous studies focused on holey graphene synthesis using CO 2 lasers (wavelength (λ) = 10,600 nm).…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, several sensing techniques like electrochemical (e.g., cyclic voltammetry and linear sweep voltammetry), enzymatic, chemical, and spectroscopy techniques have demonstrated accurate evaluation of H 2 O 2 levels. Compared to other approaches, voltammetric studies are observed to be more precise, explanatory, and cost-effective . A few previous studies report a <1 nM detection limit (LOD) for H 2 O 2 sensing; nonenzymatic H 2 O 2 sensing has demonstrated sensitivity in the micro–millimolar range. …”
Section: Introductionmentioning
confidence: 99%